Congenital pancreaticobiliary anomalies in an urban medical center in the United States. Issue 6 (15th October 2020) - Sugawa, Choichi; Culver, Ashley; Sundaresan, Naresh; Lucas, Charles E
Abstract: Background and Aim: Pancreaticobiliary anomalies are rare and often present with cryptic signs and symptoms, thus delaying appropriate treatment. Methods: Endoscopic retrograde cholangiopancreatography (ERCP) was used to define pancreaticobiliary anomalies. A retrospective review was performed of 5522 ERCPs conducted at a tertiary care center from 1972 to 2015. Results: There were 249 (4.5%) patients with pancreaticobiliary anomalies, including 179 patients with pancreas divisum (PD), 44 patients with choledochal cyst (CC) (Todani's classification Type I: extrahepatic cyst 31, Type III; choledochocele 9, Type V: Caroli's disease 4), 20 patients with anomalous pancreaticobiliary ductal union (APDU), and 6 patients with other abnormalities. Of 179 patients with pancreas divisum, 8 (4.5%) required minor sphincterotomies for multiple unexplained acute pancreatitis. Of the 31, 15 (48%) Type I CC patients underwent an operation. In patients with Type III CC (choledochocele), seven of the nine were treated by endoscopic sphincterotomy, and two patients were treated by surgery. Four patients with Type V CC (Caroli's disease) were managed nonoperatively. Of the 20 patients with APDU, 8 (40%) required operative intervention. Six patients were found to have other anomalies: two with pancreas bifidum, one with a duplication of the gallbladder, one with a cystic duct diverticulum, one with an annular pancreas, and one with an abnormal cystic duct origin. These patients were treated based on their etiology. Conclusion: Pancreaticobiliary anomalies are rare and can be defined using ERCP. The appreciation of these abnormalities is important for the proper diagnosis and treatment of these rare biliary and pancreatic disorders. Abstract : Pancreaticobiliary anomalies were analyzed using endoscopic retrograde cholangiopancreatography (5522 patients) in an urban medical center in the United States. A total of 249 (4.5%) patients were found to have a pancreaticobiliary anomaly. There were 179 patients with pancreas divisum, 44 patients with choledochal cyst, 20 patients with anomalous pancreaticobiliary ductal union, and 6 patients with other abnormalities.